Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran PBL Berbantuan Media Bigbook Pada Siswa Kelas I SD Inpres Nawaripi - Maria Nona Yani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to improve student learning outcomes in class I of SD Inpres Nawaripi by using a problem-based learning model assisted by bigbook media. The research was carried out over 3 (three) cycles, each cycle consisting of 4 (four) stages, namely planning, action, observation, and reflection/evaluation. The research instrument uses an observation sheet on the implementation of learning using the practice method and objective tests in the form of essy tests. The subjects in this research were class I students at SD Inpres Nawaripi with a total of 27 students. Subject determination is obtained based on the results of observations of the class to be studied and based on the results of referrals from the school principal. The results of this research obtained a value during the pre-cycle of 54.44, in the first cycle it increased to 63.70 and then in the second cycle the test results became 85.60, after taking action in the second cycle. The level of completion of learning outcomes in the pre-cycle reached 14.81%, the level of achievement of learning outcomes in cycle I reached 51.85%, and the level of achievement of learning outcomes in cycle II became 92.60%. Thus it can be concluded that the use of a problem-based learning model assisted by bigbook media can improve the learning outcomes of class I students at SD Inpres Nawaripi.